Lehman Brothers in the Dutch offshore financial centre: the role of shadow banking in increasing leverage and facilitating debt. Issue 3 (1st October 2016) - Fernandez, Rodrigo; Wigger, Angela
Abstract: Credit intermediation outside the regular banking system, or shadow banking, has increased immensely over the past decade. This paper situates this increase against the backdrop of the structural problem of overaccumulation, and thus the absence of profitable reinvestment opportunities in the production sphere, in addition to the scarcity of high-quality collaterals. Zooming in on Europe's offshore world and Dutch conduit structures in particular, the paper illustrates, on the basis of the Amsterdam-based Lehman Brothers subsidiary (and others), how shadow banking enables regular banks to increase leverage and take on excessive debt. It will be argued that the continued expansion of debt at the systemic level, inter alia facilitated by shadow banking, heralds the prospect of a crisis far more dramatic than the one we are currently witnessing.